(untitled) (Alternautas, 2024)
This paper focuses on UK-based cultural expressions of international solidarity with El Salvador either side of the end of the Cold War and El Salvador’s civil war. The article centres on a mural titled Changing the Picture, painted in Greenwich from 1985, which depicts a message of hope for overcoming state repression sponsored by multinational capital and Western powers; and Music for Hope, an ongoing musical education programme beginning in 1996-7 based in the Bajo Lempa, a coastal region of El Salvador, but set up and supported by a British solidarity network. After exploring the political meanings and initiatives of solidarity in the UK during the Salvadoran civil war, we analyse Changing the Picture’s central message of anti-imperialism, the depiction of collective popular struggle and the artwork’s place within the cultural politics of London in the mid-1980s. The paper then examines how the communitarian message of popular democracy present in the mural has been articulated in new cultural forms by Music for Hope, particularly through the latter’s pedagogical, horizontal and prefigurative practice of teaching music to children and adolescents and encouraging the formation of musical groups. As such, this paper foregrounds cultural and artistic practice as a central but underexplored dimension of international solidarity. Highlighting the literature on the shift in political culture, produced by the culmination of the Cold War, from a frame foregrounding revolutionary or political struggle to one centred on trauma, we explore how Changing the Picture and Music for Hope reflect different historical conditions. If the solidarity depicted in Changing the Picture reflected the final years of a period in which the revolutionary horizon was considered possible, Music for Hope emerged at a time that forced the initiative to confront the traumatic legacies of the civil war years. Despite these differences, the article argues that there is far more that connects the two examples, especially their emphasis on community agency. In doing so, we show that artistic expression can not only represent a powerful medium through which solidarity politics are communicated, condensing both local and international contexts in a radical vision of hope, but that cultural action can also structure the participatory practice frequently at the heart of international solidarity politics.